2009
DOI: 10.2215/cjn.01350209
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Renal Function and Cardiovascular Disease Risk in Obese Kidney Donors

Abstract: Background and objectives: Increasing demand for live-donor kidneys has encouraged the use of obese donors despite the absence of long-term outcome data and evidence that obesity can adversely affect renal function. We wished to determine whether obesity increased the risk for renal dysfunction and other medical comorbidities in donors several years after donation.Design, setting, participants, & measurements: Ninety-eight patients who donated a kidney 5 to 40 years previously were stratified according to body… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
63
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(69 citation statements)
references
References 45 publications
4
63
1
1
Order By: Relevance
“…Unfortunately, decreasing ney donation are appropriately stringent given that donation has short-term (23,24) and possibly long-term (25,26) risks. Obesity, which occurs more commonly among black potential donors (11)(12)(13), has uncertain long-term risks for living donors (27,28). The medical criteria for accepting living donors should not be relaxed given the ethical imperative to protect the welfare of potential and actual donors (29).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, decreasing ney donation are appropriately stringent given that donation has short-term (23,24) and possibly long-term (25,26) risks. Obesity, which occurs more commonly among black potential donors (11)(12)(13), has uncertain long-term risks for living donors (27,28). The medical criteria for accepting living donors should not be relaxed given the ethical imperative to protect the welfare of potential and actual donors (29).…”
Section: Discussionmentioning
confidence: 99%
“…Although reports suggest that the incidence of hypertension among kidney donors increases, [16][17][18][19] others have not confirmed this observation. [20][21][22][23][24] In Hong Kong, the prevalence of hypertension in the general population was 12.6% in 2014, 25 which is lower than our reported figure of 18.2%. With the progression of time after surgery, however, the prevalence of hypertension among living donors is expected to increase as age is a known influence in hypertension.…”
Section: Discussionmentioning
confidence: 77%
“…Several small retrospective studies have shown that there is no increased risk of deterioration in renal function in obese patients who donate a kidney during the first 5 years after surgery. [27][28][29] However, the follow-up duration was short, and these studies all concluded that overweight and obese kidney donors need intensive preoperative education and postoperative health maintenance. On the other hand, a recent cohort study of over 95 000 patients who underwent living-donor nephrectomy for kidney transplant demon strated an increased risk of end-stage renal disease over a median 7.6 years versus that shown in matched healthy nondonors.…”
Section: Discussionmentioning
confidence: 99%